Soft skills development in future foreign language teachers: evidence from digital educational artifacts - Akbike Boranbayeva; Gulnur Yerik; Svetlana Minasyan (International Journal of Evaluation and Research in Education (IJERE), 2026)
In the context of digital transformation in teacher education, the development of soft skills among future foreign language teachers has become an important dimension of professional preparation. This qualitative case study aimed to identify the factors shaping soft skills development through the analysis of digital educational artifacts created in a technology-enhanced learning environment. The study involved 48 undergraduate students enrolled in a foreign language teacher education program during one academic semester. The data corpus included reflective essays, discussion posts, collaborative project outputs, multimedia assignments, and digital portfolios produced within a learning management system (LMS)-based course. Content analysis and thematic coding were used to identify recurring patterns in the artifacts. The findings revealed five interrelated groups of factors influencing soft skills development: pedagogical design and teaching methods, pedagogical strategies and learning activities, communication and collaboration in digital environments, organization and management of learning activities, and professional and personal development. The results show that digital educational artifacts provide rich evidence of authentic soft skills manifestation beyond traditional self-report methods. The proposed five-factor model may serve as a practical framework for teacher educators and curriculum designers in digitally mediated teacher education.